The Influence of Instructional Leadership and Teacher Digital Literacy on the Quality of In-Depth Learning in Public Elementary Schools - Novia Indriyani; Widya Kusumaningsih; Ngurah Ayu Nyoman M (Sakura Digital Nusantara, 2026)
Purpose: The purpose of this study is to: determine the magnitude of the influence of instructional leadership and teachers' digital literacy together on the quality of in-depth learning. Methods: The research approach used is quantitative. This type of research uses correlation research. The population of this study was 244 teachers and the research sample was 152 teachers. Data collection was carried out using a questionnaire. The data analysis techniques used in this study were descriptive data analysis, prerequisite tests including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests including simple and multiple linear regression. Findings: The results of the study showed that: (1) the correlation of instructional leadership on the quality of in-depth learning was 0.824. The influence of instructional leadership had a significant effect on the variable of the quality of in-depth learning by 78.0%. (2) The correlation of teachers' digital literacy on the quality of in-depth learning was 0.960. The influence of teacher digital literacy has a significant effect on the variable of in-depth learning quality by 92.1%. (3) Then the correlation coefficient value r is 0.963. The result of the coefficient of determination of the influence of variables X1 and X2 on Y is 92.7%. Research implications: This study suggests that optimizing principals’ instructional leadership and enhancing teachers’ digital literacy can improve the quality of in-depth learning. Originality: This research uniquely examines the combined role of instructional leadership and teachers’ digital literacy in influencing in-depth learning quality at the elementary school level, a topic rarely explored.